Water transport during bread baking: Impact of the baking temperature and the baking time - Ureta, María Micaela (2018)
The impact of the baking temperature on the moisture profile (in terms of water content), during bread baking was analyzed using a convection oven (three oven temperatures and different baking times). During baking, local water content and temperature were measured at different regions of the crust and crumb. There was found an increase in water content at the core. Water content reached a maximum level (at about 2.5%), with no effect of the baking temperature, and decreased slowly at advanced baking times. Regarding the crust, a theoretical model relating water flux to the driven force (temperature difference between the oven environment and the vaporization front) and the crust thermal resistance was validated with experimental values. Water losses were also reported. The water lost by bread contributes significantly to the energy consumption by this process and its reduction is of concern for conducting the process in a more sustainable manner. A better optimization of heat transfer between the surface (for coloration purposes) and the core (for inflation purposes) could help in this way, together with shorter baking duration and hence higher yield.